AVALIAÇÃO DA CAPACIDADE FUNCIONAL EM PORTADORES DE INSUFICIÊNCIA RENAL CRÔNICA QUE NÃO REALIZAM HEMODIÁLISE - Dallazen, Fernanda; Belli, Karlyse C.; Pertile, Kelly P.; Szymczak, Leticia; Basso, Olvânia; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo